A Randomized Pilot Trial of Contingency-management Intervention for Patients in during Methadone Maintenance Treatment, Cash vs. Vouchers - Bijan PIRNIA; Ali SOLEIMANI; Hamid Reza TAHERINAKHOST; Kambiz PIRNIA; Parastoo MALEKANMEHR; Alireza ZAHIRODDIN (Tehran University of Medical Sciences, 2018)
No Abstract###